A prospective cohort study investigating an exposure-response relationship among vibration-exposed male workers with numbness of the hands - Maria Edlund; Lage Burström; Lars Gerhardsson; Ronnie Lundström; Tohr Nilsson; Helena Sandén; Mats Hagberg (Nordic Association of Occupational Safety and Health (NOROSH), 2014)
OBJECTIVE: The aim of this study was to investigate the exposure-response relationship of hand-arm vibration exposure to neurological symptoms (numbness) of the hand in a cohort of vibration-exposed workers. METHODS: The baseline cohort comprised 241 office and manual workers with and without exposure to hand-arm vibration. Numbness (the symptom or event) in the hand was assessed for all subjects at baseline and follow-ups after 5, 10, and 16 years. The workers were stratified into quartiles with no exposure in the first quartile and increasing intensity of exposure in quartiles 2-4 (groups 1-3). Data analysis was performed using survival analysis (time to event). Information on cumulative exposure and years of exposure to event was collected via questionnaires. Measurements were performed in accordance with the International Organization for Standardization (ISO) 5349-1. RESULTS: The hazard ratio (HR) of risk of event (numbness) differed statistically significantly between the non-exposed group (group 0) and the two higher exposure groups (groups 2 and 3). There was also a significant ratio difference between the lowest exposure group (group 1) and the two higher groups. The ratio for group 1 was 1.77 [95% confidence interval (95% CI) 0.96-3.26] compared with 3.78 (95% CI 2.15-6.62) and 5.31 (95% CI 3.06-9.20) for groups 2 and 3, respectively. CONCLUSION: The results suggest a dose-response relationship between vibration exposure and numbness of the hands. This underlines the importance of keeping vibration levels low to prevent neurological injury to the hands.